Penguatan Nilai-Nilai Pluralisme dalam Pola Relasi Sosial - Hayat Hayat (LPPM IAIN Sultan Amai Gorontalo, 2016)
Indonesia is a pluralistic and multicultural nation. Mutliculturalism in Indonesia is characterized by the recognition of religious diversity. Therefore, differences are owned by Indonesia is a realistic conception that should continue in the wake and be empowered, as a reinforcement to the life and well-being for the people of Indonesia are harmonious and dynamic. The purpose of this study was to describe the strengthening of the values of pluralism and describe and understand the relationship pattern social conducted by the government, religious and community leaders in the prevention of the onset of horizontal conflict. This research was conducted with qualitative research using describtive approach, which describes the results of research appropriate to the purpose of research and followed by data analysis to obtain relevant and accurate data. Techniques of data collection are done by using literature review that support in answering this research problem. Horizontal conflict handling quite restrained and well. Aspects of tolerance have an important role of cooperation between the government and the religious leaders to support the acceleration of meaning and substance tolerance transformed into social life, so that conflicts can be avoided with a pattern horizontally comprehensively realization.